Optimized delta sigma modulation for Class-S power amplifiers based on GaN switching transistors - Samulak, A.; Fischer, G.; Weigel, R. (2009 IEEE Radio and Wireless Symposium, 2009)
A novel modulation concept based on Delta-Sigma modulation dedicated for a Class-S Amplifier based on GaN technology is presented. This paper includes system considerations of efficient modulation schemes for GaN switching transistors, which suffer from many limits. The analyses are focused on evaluating the impact of modulation scheme on the switching conditions of the transistors. Moreover practical figures of merits are introduced for defining optimum modulation strategy. Simulations are performed for a carrier frequency of 890.88 MHz for UMTS 5 MHz bandwidth signal. Results describe the main differences and limits of modulation schemes dedicated for switching mode power amplifiers.